Preliminarii la ancheta pe tema percepției și participării politice - Mărginean, Ioan (Calitatea Vieții, 1991)
Applied to a sample of about 1,246 persons over 18, who worked (or learned) in town, the inquiry took place in the post-revolutionary period, a period with undefinite structures and electoral disputes. Without having in view to request the electoral options, the operational research scheme consisted in: the perception of the political situation (the behaviour of the politicians, Parliament, government and parties); the satisfaction/unsatisfaction degree (frustration, alienation) in the political sphere; the prospects of the near and distant future; the options concerning the economic reforms; the political participation.